Abuse of sinemet® (levodopa/carbidopa combination) in a patient with schizophrenia - Arslan, Derya; Tuman, Taha Can; Çakır, Uğur; Yıldırım, Osman (Journal of Dependence, 2016)
Sinemet® is a combination of carbi-dopa and levodopa (L-dopa) that is used to treat Parkinson’s disease and syndrome. L-dopa is considered the gold standard of drug therapies for the treatment of Parkinson’s disease because it is the metabolic precursor of dopamine, crosses the blood-brain barrier, and is presumably converted to dopamine in the brain. Drug abuse is the patterned use of a substance (drug) in which the user consumes the substance in amounts or through methods not supported by the advice of medical professionals. Patients with Parkinson’s disease require escalations in the dose of the dopamine agonists that are used to treat this disease as it progresses, and it is possible that this may lead to psychological dependence and abuse as the dose increases. The abuse potential of anticholinergic drugs is well known, but there is limited research regarding the abuse potential of dopamine agonists in the medical literature. Thus, in this case report, it was aimed to discuss abuse of Sinemet® in a patient with schizophrenia.